Beyond the Limits: tRNA Array Units in Mycobacterium Genomes - Morgado, Sergio M.; Vicente, Ana C. P. (Frontiers in Microbiology, 2018)
tRNA array unit, a genomic region presenting an intriguing high tRNA gene number and density, was supposed to occur only in few bacteria phyla, particularly Firmicutes. Here, we identified and characterized an abundance and diversity of tRNA array units in Mycobacterium associated genomes. These genomes comprised chromosome, bacteriophages and plasmids from mycobacteria. Firstly, we had identified 32 tRNA genes organized in an array unit within a mycobacteria plasmid genome and therefore, we hypothesized the presence of such structures in Mycobacterium genus. However, at the time, bioinformatics tools only predict tRNA genes, not characterizing their arrangement as arrays. In order to test our hypothesis, we developed and applied an in-house Perl script that identified tRNA genes organization as an array unit. This survey included a total of 7670 complete and drafts genomes of Mycobacterium genus, 4312 mycobacteriophage genomes and 40 mycobacteria plasmids. We showed that tRNA array units are abundant in genomes associated to the Mycobacterium genus, mainly in Mycobacterium abscessus complex species, being spread in chromosome, prophage and plasmid genomes. Moreover, other non-coding RNA species (tmRNA and structured RNA) were also identified in these regions. Our results revealed that tRNA array units are not restrict, as previously assumed, to few bacteria phyla and genomes being present in one of the most diverse bacteria genus. We also provide a bioinformatics tool that allows further exploration of this issue in huge genomic databases. The presence of tRNA array units in plasmids and bacteriophages, associated with horizontal gene transfer, and in a bacteria genus that explores diverse niches, are indicatives that tRNA array units have impact in the bacteria biology.